Compendium of Social Statistics and Indicators : Social Indicators of The Commission of Sustainable Development (United Nations, 2007)
﻿Sustainable development has been recognized as a cross-cutting issue and basic pillar for improving lives and ensuring peace and prosperity. The eighth issue of the Compendium focuses on the social indicators of the Commission of Sustainable Development (CSD), being a cross-cutting topic in international frameworks and of relevance to the ESCWA region. A reduced list of indicators is presented in accordance with regional development priorities. Data were mainly compiled from national statistical offices and supplemented with international data. Country-specific and cross-country analyses show that the ESCWA countries have made significant improvements in many social indictors of the CSD framework since the 1990s. Notwithstanding this progress, efforts are needed to address intraregional disparities, the gender gap, and the urban-rural divide, in addition to overcoming data limitations in some areas in order to support evidence-based policymaking for sustainable development in the region.